Challenging the addiction/health binary with assemblage thinking: An analysis of consumer accounts - Moore, David; Pienaar, Kiran; Dilkes-Frayne, E.; Fraser, Suzanne (Elsevier BV, 2017)
Critical analyses of drug use and 'addiction' have identified a series of binary oppositions between addiction and free will, independence, self-control, responsibility, productivity and autonomy. This critical work has also examined how science, policy and popular discourses frequently characterise addiction as antithetical to health and well-being. Furthermore, those diagnosed with addiction are often understood as indifferent to health and well-being, or as lacking the knowledge or desire required to maintain them. In this article, we draw on data from 60 qualitative interviews with people who self-identify as living with an 'addiction', 'dependence' or 'habit', to argue that the binary opposition between addiction and health struggles to attend to their rich and varied health perspectives and experiences. We explore three themes in the interview data: reinscribing the binary opposition between addiction and health/well-being; strategies for maintaining health and well-being alongside addiction; and alcohol and other drug consumption as aiding health and well-being. Perhaps because addiction and health have been so thoroughly understood as antithetical, such perspectives and experiences have received surprisingly little research and policy attention. Yet they offer fertile ground for rethinking the strengths and capacities of those who self-identity as living with an addiction, dependence or habit, as well as untapped resources for responding to the harm sometimes associated with alcohol and other drug use.